UNA EXPERIENCIA PARA PROMOVER LA INOCUIDAD ALIMENTARIA EN UNA ESCUELA AGROPECUARIA - Lampert, D (Universidad Nacional del Litoral, 2022)
This article relates, as educational proposal an extension experience that, in addition, was part of the Supervised Professional Practice of a Food Engineering student, on the assurance of safety in an agricultural school. The way to act and these arch for solutions to develop educational proposals in relation to the subjectis detailed. So much so that workshops and advice were hel don facilities, food handling and food production. Among the associated practices, we worked in a multidisciplinary way, with other agricultural professionals and veterinary medicine students, to develop joint proposals.